The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/smll.202205797
|View full text |Cite
|
Sign up to set email alerts
|

Triple Stimuli‐Responsive Flexible Shape Memory Foams with Super‐Amphiphilicity

Abstract: source. Ko et al. construct a temperature-responsive SMP film by integrating polylactic acid (PLA) and thermoplastic polyurethane (TPU). [15] Ni et al. simply adjust the layers of graphene oxide coating on SMP to design thermal-responsive devices. [16] However, the single responsive ability cannot meet the requirement of increasingly complex and changeable application environment. [17][18][19] On the other hand, the solid planar or strip geometries of traditional SMPs limit the expansion of new horizons. [20][… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 79 publications
(102 reference statements)
0
4
0
Order By: Relevance
“…Once a cross-linked network is formed, its permanent shape cannot be changed. However, for vitrimer containing dynamic ester bonds, thermally induced dynamic transesterification imparts configurable memory properties to the material, offering possibilities for reshaping the curing material. , As shown in Figure c, when compressed from its original diameter of 34 to 15 mm, it was observed that the EPC foam could be perfectly restored to its initial state of 34 mm after heating at 120 °C and removal of external force, indicating its exceptional shape memory properties. , Additionally, in Figure d, a rectangular-shaped foam could be temporarily reshaped into an “n” shape by heating it to 120 °C (above T g ). After cooling to room temperature, the foam maintained its temporary “n” shape.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Once a cross-linked network is formed, its permanent shape cannot be changed. However, for vitrimer containing dynamic ester bonds, thermally induced dynamic transesterification imparts configurable memory properties to the material, offering possibilities for reshaping the curing material. , As shown in Figure c, when compressed from its original diameter of 34 to 15 mm, it was observed that the EPC foam could be perfectly restored to its initial state of 34 mm after heating at 120 °C and removal of external force, indicating its exceptional shape memory properties. , Additionally, in Figure d, a rectangular-shaped foam could be temporarily reshaped into an “n” shape by heating it to 120 °C (above T g ). After cooling to room temperature, the foam maintained its temporary “n” shape.…”
Section: Resultsmentioning
confidence: 97%
“…53,54 As shown in Figure 5c, when compressed from its original diameter of 34 to 15 mm, it was observed that the EPC foam could be perfectly restored to its initial state of 34 mm after heating at 120 °C and removal of external force, indicating its exceptional shape memory properties. 55,56 Additionally, in Figure 5d, a rectangular-shaped foam could be temporarily reshaped into an "n" shape by heating it to 120 °C (above T g ). After cooling to room temperature, the foam maintained its temporary "n" shape.…”
Section: Mechanical and Thermal Properties Of Epc-xmentioning
confidence: 99%
“…Specific 4D printed structures can respond to multiple stimuli based on the composition of the smart structure, which can be a smart composite or a smart material with different fillers. [ 171 ] We will only focus on physical and chemical stimulation, as little information is available regarding the 4D printing of biologically responsive materials.…”
Section: D Printing Processmentioning
confidence: 99%
“…Compared with thermo‐active SMPs, electro‐active shape memory polymer composites (SMPCs) have the characteristics of easy control, remote drive and fast response, which made them more suitable for biomedical and micro‐level applications 15–17 . The electro‐active SMPCs is a composite material containing with conductive fillers such as graphene oxide, 18 carbon nanotubes (CNT), 19,20 carbon black, 21,22 carbon fiber, 23,24 and silver nanowires 25,26 . Among them, CNT have excellent thermal and electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] The electro-active SMPCs is a composite material containing with conductive fillers such as graphene oxide, 18 carbon nanotubes (CNT), 19,20 carbon black, 21,22 carbon fiber, 23,24 and silver nanowires. 25,26 Among them, CNT have excellent thermal and electrical conductivity. Particularly, singlewalled carbon nanotubes (SWCNT) have the advantages of small diameter distribution range, few defects and high uniformity, which contribute to the excellent physical properties and chemical versatility of the materials.…”
Section: Introductionmentioning
confidence: 99%